Entrepreneurial competences, liability of newness and infant survival: Evidence from the service industry. Issue 9 (10th October 2016) - Abatecola, Gianpaolo; Uli, Vincenzo
Abstract : Purpose: What entrepreneurial competences can increase the start-ups' infant survival chances? How can the liability of newness be successfully handled? Positioned in this research stream, which, especially over recent years, has been particularly lively also in the Journal of Management Development, the purpose of this paper is to meet not only the research, but also the education and practice-oriented purposes of the journal. Design/methodology/approach: How can routines' exploitation counteract the liability of newness? How can entrepreneurial orientation oppose it? Why is the liability of adolescence important when discussing the performance of start-ups? To address these questions, taken separately into account, the paper presents a set of three case studies from the service industry, each of which is based on a specific research design. Findings: The authors found that the routines' exploitation mechanisms, the degree of entrepreneurial orientation of the founding team, and the stock of the initial assets, could be all considered consistent predictors of new ventures' infant survival. The authors thus believe that the findings may offer a useful contribution both to current and prospective managers and entrepreneurs. Originality/value: Stinchcombe's assumption about the tremendous failure rate associated with the earliest stage of start-ups' life cycle has been proved to be valid at least in the most recent evidence from both Europe and the USA. At the same time, formalizing a checklist of competences appropriate to increase the possibilities of organizational infant survival appears as a priority not yet accomplished. Thus, the study is aimed at providing some useful food for thought on this issue.